Circulation of avian influenza viruses in wild birds in Inner Niger Delta, Mali - (:unkn) unknown (My University, 2012)
Please cite this paper as: Cappelle et similar to al. (2012) Circulation of avian influenza viruses in wild birds in Inner Niger Delta, Mali. Influenza and Other Respiratory Viruses 6(4), 240244. Background Avian influenza viruses (AIV) have been detected in wild birds in West Africa during the northern winter, but no information is available on a potential year-round circulation of AIV in West Africa. Such year-round circulation would allow reassortment opportunities between strains circulating in Afro-tropical birds and strains imported by migratory birds wintering in West Africa. Objective and Method A 2-year longitudinal survey was conducted in the largest continental wetland of West Africa, the Inner Niger Delta in Mali, to determine the year-round circulation of AIV in wild birds. Results and Conclusions Avian influenza virus RNA was detected during all periods of the year. Very low prevalence was detected during the absence of the migratory wild birds. However, a year-round circulation of AIV seems possible in West Africa, as shown in other African regions. West Africa may hence be another potential site of reassortment between AIV strains originating from both Afro-tropical and Eurasian regions.
Keywords: African Research